Метод імітації водного стресу на Arabidopsis thaliana L. - Bobrownyzky, J. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2006)
A method for the imitation of drought stress in Arabidopsis thaliana L. combining the advantages of rapid and prolonged treatments was developed. The proposed method allows decreasing water content in the growth medium gradually and homogenously, growing plants under sterile conditions, and observing a root system during the growth. In the course of experiment, gradual growth retardation of stressed plants was observed. The rates of cell division and cell elongation of the tap root were measured and it was defined that cell division and cell elongation are both responsible for growth retardation. Morphological changes in the roots of stressed plants were described.